Arabinoxylan/graphene‐oxide/nHAp‐NPs/PVA bionano composite scaffolds for fractured bone healing. (9th March 2021) - Aslam Khan, Muhammad Umar; Haider, Adnan; Abd Razak, Saiful Izwan; Abdul Kadir, Mohammed Rafiq; Haider, Sajjad; Shah, Saqlain A.; Hasan, Anwarul; Khan, Rawaiz; Khan, Salah‐ud din; Shakir, Imran
Abstract: The importance of bone scaffolds has increased many folds in the last few years; however, during bone implantation, bacterial infections compromise the implantation and tissue regeneration. This work is focused on this issue while not compromising on the properties of a scaffold for bone regeneration. Biocomposite scaffolds (BS) were fabricated via the freeze–drying technique. The samples were characterized for structural changes, surface morphology, porosity, and mechanical properties through spectroscopic (Fourier transform‐infrared [FT‐IR]), microscopic (scanning electron microscope [SEM]), X‐ray (powder X‐ray diffraction and energy‐dispersive X‐ray), and other analytical (Brunauer–Emmett–Teller, universal testing machine Instron) techniques. Antibacterial, cellular, and hemocompatibility assays were performed using standard protocols. FT‐IR confirmed the interactions of all the components. SEM illustrated porous and interconnected porous morphology. The percentage porosity was in the range of 49.75%–67.28%, and the pore size was 215.65–470.87 µm. The pore size was perfect for cellular penetration. Thus, cells showed significant proliferation onto these scaffolds. X‐ray studies confirmed the presence of nanohydroxyapatite and graphene oxide (GO). The cell viability was 85%–98% (BS1–BS3), which shows no significant toxicity of the biocomposite. Furthermore, the biocomposites exhibited better antibacterial activity, no effect on the blood clotting (normal in vitro blood clotting), and less than 5% hemolysis. The ultimate compression strength for the biocomposites increased from 4.05 to 7.94 with an increase in the GO content. These exciting results revealed that this material has the potential for possible application in bone tissue engineering.